PEMBERDAYAAN ANAK PENYANDANG DISABILITAS DALAM MENINGKATKAN LIFE SKILL MELALUI PENERAPAN SISTEM AKUAPONIK - Brilianita Puspa Putri Anggun Rusady; Ramadio Akbar Saputra; Aranssa Dwiveronikca Rajagukguk; Dormauli Sijabat; Putri Nanda Ika Ariyanto; Marjam Desma Rahadhini (Lembaga Penelitian dan Pengabdian Masyarakat, 2022)
Children with disabilities are part of diversity, but there are problems such as the lack of character formation of children, not yet optimal in developing the potential and limited skills and independence of children with disabilities. So the PKM-PM team at Slamet Riyadi University Surakarta provided a mentoring activity through the application of the aquaponics system in order to empower children with disabilities in improving the life skills of children with disabilities at YPAC Professor Doctor Soeharso Surakarta. The methods applied in this service include: (1) providing counseling and socialization related to the aquaponics system, (2) aquaponics assembly, (3) training related to aquaponics seeding and care, and (4) monitoring the development of aquaponics. The result of this service is that children with disabilities who become participants during the service process have gained knowledge related to the aquaponics system. Children routinely carry out maintenance such as spraying hydroponic vegetables, feeding catfish to cleaning fish waste at the bottom of the pond. Assistance is carried out to train the independence and responsibility of children with disabilities in aquaponic care as well as become vocational skills for them which if aquaponics continues to be developed it will become a source of income for children with disabilities, especially those living in dormitories. This service has achieved the expected results and the sustainability of this program continues to be carried out with a monitoring pattern. Keywords: Aquaponics, Empowerment, Children with Disabilities, Life Skills